(untitled) (Academicia Globe: Inderscience Research, 2022)
This article is one of the important changes aimed at increasing the literacy of children, which is the basis of the third Renaissance - the textbooks of the 1st grade students in their native language, textbooks by the Ministry of State Education the book "Mother tongue and growth is literate" was transformed into a single book. This change is about whether or not students are comfortable with the learning process.